Plasma levels of adipokines in patients with Alzheimer's disease - where is the "breaking point" in Alzheimer's disease pathogenesis? - Vaňková, M; Vacínová, G; Včelák, J; Vejražková, D; Lukášová, P; Rusina, R; Holmerová, I; Jarolímová, E; Vaňková, H; Bendlová, B (Physiological research, 2020)
Peripheral insulin resistance is associated with decreasing adiponectin and increasing leptin plasma levels, and also with cognitive decline. The effects of adipokines on brain function have been published from both animal and human studies. In particular, the influence of leptin and adiponectin on the development of Alzheimer's disease (AD) has been extensively investigated. However, the association between adipsin and AD is as yet unknown. In 37 patients with AD and 65 controls that followed the same study protocol, we tested whether adiponectin, leptin, and adipsin could be used as biomarkers in the early stages of AD. In contrast with conclusions of cognition studies in insulin resistant states, our study found a correlation of impaired neuropsychological performance with increasing adiponectin and decreasing leptin in AD patients. Nevertheless, no significant differences between patients and controls were found. AD women had significantly increased adipsin compared to controls, and there was a positive correlation of adipsin with age and disease duration. Although adipokines do not appear to be suitable biomarkers for early AD diagnosis, they certainly play a role in the pathogenesis of AD. Further studies will be needed to explain the cause of the adipokine "breaking point" that leads to the pathogenesis of overt AD.
Keywords: leptin; adiponektin; Adiponectin; Middle Aged; mužské pohlaví; studie případů a kontrol; Alzheimer Disease; Leptin; Complement Factor D; komplement - faktor D; ženské pohlaví; Humans; biologické markery; lidé středního věku; Alzheimerova nemoc; Case-Control Studies; Biomarkers; Female; lidé; Male